In vitro display evolution of unnatural peptides spontaneously cyclized via intramolecular nucleophilic aromatic substitutions. Issue 34 (7th April 2022) - Yokoyama, Takumi; Ando, Takehiro; Takamori, Yukio; Fuji, Daisuke; Sato, Masashi; Vedi, Santhana; Yamamoto, Mizuki; Kawakami, Takashi
Abstract : We report novel spontaneous peptide cyclization by intramolecular nucleophilic aromatic substitutions using ribosomally incorporatable and intramolecularly cysteine-reactive fluorobenzoic acid-derived linkers. Abstract : We report novel, ribosomally incorporatable, and intramolecularly cysteine-reactive fluorobenzoic acid-derived linkers for SELEX of mRNA-displayed unnatural peptides, which spontaneously cyclized via intramolecular nucleophilic aromatic substitutions forming thioethers. With this strategy we identified several novel PCSK9-binding peptides.